Expanding The UTAUT 2 Framework: The Role of Occupational Background in Technology Adoption for Social Security Services in Indonesia - Sukma, Hilwa Mutiara; Akbar, Gugun Geusan; Karmila, Mila (Yayasan Ilomata, 2025)
The digital competence of Indonesian society in 2024 is quite good. However, adopting digital technology in social security services still faces various obstacles, especially in improving the JMO application's effectiveness, which BPJS Ketenagakerjaan participants still complain about. This study aims to investigate and evaluate user acceptance of the JMO application. The research employs the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2), along with Multi-Group Analysis (MGA) and Importance-Performance Map Analysis (IPMA), to obtain a thorough understanding of the factors affecting user acceptance of the JMO application. A quantitative approach was adopted, involving the distribution of online questionnaires to JMO users across various regions in Indonesia. The study employed a purposive sampling method to gather data from 153 respondents. The data was analyzed using the SmartPLS 3 software, which revealed that factors including Effort Expectancy, Performance Expectancy, and Social Influence significantly impact users’ intentions to adopt the application. These factors also shape users' behavior when utilizing the JMO application. The findings underscore the importance of prioritizing key aspects such as user comfort and ease of access in the development and maintenance of the application. By addressing these critical factors, the implementation of the JMO has the potential to achieve long-term success and encourage the provision of fairer and more equitable social security protection for all Indonesian workers.